Arduino prototyping inputs : building and testing your ideas (O'Reilly, 2016)
"Artists, product designers, and inventors who understand the basics of Arduino prototyping can take their skills to the next level in this overview of how to work with input sensors: those multitude of devices that can monitor the physical world. You'll start with the simple (temperature sensors, light sensors) and then move up to the complex (distance, accelerometer, object recognition), learning how each sensor functions, how to wire them up, and how to program them."--Resource description page.